Big Brown : - Niemann, Greg (Jossey-Bass, 2007)
"UPS founder Jim Casey did more than overcome humble beginnings to achieve the American Dream—he inspired all of his employees to come along for the ride. The continuous success of a company founded on a hundred dollars, determination, and integrity is a story of inspiration. Big Brown is a must-read for anyone who's ever held a job or had a dream." —Paul Casey, nephew of UPS founder Jim Casey